The middle class and the development process - Solimano, Andrés (CEPAL [Santiago]CL, 2008)
Investigates, for a sample of more that 120 countries, some empirical correlates between the size of the middle class and the following set of variables : the level (mean) of per capita income and wealth, the degree of inequality (Gini coeffients) of per capita income and wealth, the level and composition of public expenditure, the share of small and medium size enterprises in employment and ouput and an indicator of democracy.